Immunogenicity and reactogenicity of accelerated regimens of fractional intradermal COVID-19 vaccinations - Niyomnaitham, Suvimol; Atakulreka, Suparat; Wongprompitak, Patimaporn; Copeland, Katherine Kradangna; Toh, Zheng Quan; Licciardi, Paul V.; Srisutthisamphan, Kanjana; Jansarikit, Laddawan; Chokephaibulkit, Kulkanya (Frontiers in Immunology, 2023)
This phase I study explored the immunogenicity and reactogenicity of accelerated, fractional, intradermal vaccination regimens for COVID-19. Participants (n = 60) aged 18-60 years, naïve to SARS-CoV-2 infection or vaccination, were randomly allocated into one of four homologous or heterologous accelerated two-dose, two-injection intradermal regimens seven days apart: (1) BNT162b2-BNT162b2 (n = 20), (2) ChAdOx1-BNT162b2 (n = 20), (3) CoronaVac-ChAdOx1 (n = 10), and (4) ChAdOx1-ChAdOx1 (n = 10). CoronaVac and ChAdOx1 were 20%, and BNT162b2 17%, of their standard intramuscular doses (0.1 mL and 0.05 mL per injection, respectively). Humoral immune responses were measured through IgG response towards receptor binding domains (RBD-IgG) of ancestral SARS-CoV-2 spike protein and pseudovirus neutralization tests (PVNT50). Cellular immune responses were measured using ELISpot for ancestral protein pools. Immunogenicity was highest in regimen (2), followed by (1), (4), and (3) 2 weeks after the second dose (P < 0.001 for anti-RBD-IgG and P = 0.01 for PVNT50). Each group had significantly lower anti-RBD IgG (by factors of 5.4, 3.6, 11.6, and 2.0 for regimens (1) to (4), respectively) compared to their respective standard intramuscular regimens (P < 0.001 for each). Seroconversion rates for PVNT50 against the ancestral strain were 75%, 90%, 57% and 37% for regimens (1) to (4), respectively. All participants elicited ELISpot response to S-protein after vaccination. Adverse events were reportedly mild or moderate across cohorts. We concluded that accelerated, fractional, heterologous or homologous intradermal vaccination regimens of BNT162b2 and ChAdOx1 were well tolerated, provided rapid immune priming against SARS-CoV-2, and may prove useful for containing future outbreaks.